Penegakan Hukum terhadap Tindakan Penyalahgunaan Kekuasaan dalam Kondisi Darurat Covid-19 - Hasanal Mulkan (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study will look at the government's policy of handling Covid-19 from a prophetic legal point of view based on three main pillars, namely humanization, liberation and transcendence. In this study, the authors use normative research by using the approach to legislation, the prophetic legal concept approach and the case approach. The results of the study show that the Covid-19 handling policy carried out by the government still contains inaccurate recipient data, the distribution of basic needs assistance is not carried out in stages from the Central Government to the Regional Government but is carried out simultaneously, there is a legal basis that opens space abuse of authority due to legal immunity for officials. Keywords: Policies, handling of covid-19, prophetic lawThe government has issued several legal products such as Government Regulation in Lieu of Law Number 1 of 2020 concerning State Financial Policy and Financial System Stability for Handling the Corona Virus Disease 2019 (COVID-19) Pandemic and/ Or in the context of Facing Threats That Endanger the National Economy and/or Financial System Stability and Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions (PSBB) in the Context of Accelerating Handling of Corona Virus Disease 2019 (COVID-19). The government has also implemented PSBB and Physical Distancing policies, but these policies are not effective in breaking the chain of spread of COVID-19, it can be seen that the number of COVID-19 cases in Indonesia on January 28, 2021 has reached 1 million cases, the highest in Southeast Asia.